Formulasi Orally Disintegrating Tablet (ODT) Furosemide Menggunakan Fast Disintegrant Crospovidone dan Croscarmellose Sodium dengan Metode Kempa Langsung - Prastika, Delia Ayu; Rejeki, Endang Sri; Priyanto, Widodo (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Orally Disintegrating Tablets (ODT) are tablets that disintegrate or break down in less than one minute. Furosemide is a potent diuretic (loop diuretic) used in the treatment of edema associated with hypertension, congestive heart disease, heart failure, liver cirrhosis and kidney disease. Crospovidone is a fast disintegrating agent which is very porous so it can speed up the tablet disintegration time. Croscarmellose sodium is able to absorb water and expand quickly, thereby accelerating the disintegration of the tablet. The aim of this research was to determine the effect of the fast disintegrants crospovidone and croscarmellose sodium on the physical properties and dissolution profile of furosemide ODT, and to find out which fast disintegrant is better in producing good furosemide ODT. This study used seven formulas, namely three formulas with variations of crospovidone 1%, 3% and 5%, three formulas with variations of crosscarmelosse sodium 1%, 3% and 5% and one formula as a control. Furosemide ODT is made by direct compression method. Evaluation of the physical properties of furosemide ODT includes hardness test, brittleness test, and disintegration time test. Tablet dissolution profile testing was carried out in-vitro. The data obtained were analyzed using the one way ANOVA test with a confidence level of 95%. The results showed that the addition of rapid disintegrating crospovidone and croscarmellose sodium at a concentration of 5% was able to influence the hardness, friability and disintegration time of the tablet, as well as increasing the dissolution profile. A better rapid disintegrating agent that produces good furosemide ODT is croscarmellose sodium.